Neraca Keseimbangan pada Sumberdaya dan Cadangan Bijih Bauksit serta Bijih Nikel di Indonesia - Rosyadi, Muhammad Bahtiyar; Wardhana, Novandri Kusuma (ReTII, 2019)
The government in the context of adding information on the wealth of natural resources in this connection is iron ore and nickel ore in Indonesia, as well as economic forecasts and analysis which are not periodically owned by the stakeholders. Data validation of iron sand and nickel resources has not been documented accurately because there is no coordination and synchronization of companies and associations - very diverse, different from other agencies or institutions. From the analysis it is known that the initial value of bauxite resources in 2017 amounted to 1.72 billion tons exploited by 1.15 million tons, the discovery of new exploration results amounted to 2.33 billion tons, to be the final balance of 4.45 billion tons with the price of bauxite resources of US 289.83 billion. New exploration results were 1.94 billion tons and the final balance was 5.65 billion tons, with a nickel ore price of US 29, the economic value of nickel resources was US 164.08 billion. The results of the analysis are expected to provide benefits as a database in the management of bauxite and nickel ore resources.